First, let's put that line in standard form
y - 3 = 3(x + 1)
y - 3 = 3x + 3
y = 3x + 6
(Standard form is y = mx+b, where m is slope and b is y-intercept.)
Now, a line parallel to that line would have the same slope of 3. So now we have m = 3. Plug that in for m and now we have
y = 3x + b
But we still need the b value. We can get that by plugging in the point (0, -3)
(-3) = 3(0) + b
-3 = 0 + b
b = -3
Now put b back into the equation and your final equation is
y = 3x - 3
Answer:
Whole number, integer, rational
Step-by-step explanation:
C, because as x increases y increases by a factor of 2. There is a constant value ( 2 ) which is being times to y in every value for x. So y is a constant multiple of x because x is always being multiplied by 2.